SCREENING AND EVALUATION OF VARIOUS CARBON SOURCES ON THE ABILITY OF TRICHODERMA HARZIANUM INACC TO SOLUBILIZE INSOLUBLE PHOSPHATE - Napitupulu, Toga P.; Ilyas, Muhamad; Kanti, Atit; Sudiana, I. Made (JURNAL BIOLOGI INDONESIA, 2019)
ABSTRACTOur previous works revealed that Trichoderma harzianum InaCC (Indonesian Culture Collection) produced volatile organic compounds that inhibited the growth of Fusarium oxysporum. The objective of this study was to evaluate the ability of T. harzianum InaCC to solubilize insoluble phosphate and optimize the carbon sources condition. Screening was conducted to 10 isolates of T. harzianum on Pikovskaya?s broth in 100-mL conical flasks. The cultures were incubated at 30 ± 1°C for  7 days on a rotary shaker at 80 r/min. All  T. harzianum isolates were observed for the solubility of insoluble tricalcium phosphate with the highest ability was performed by T. harzianum InaCC F88. Using this isolate, the optimization of insoluble phosphate solubilization was conducted on modifed Pivoskaya medium in 500-mL conical flasks in similar screening incubation condition with applying of different combination of phopshate sources (tricalcium phosphate and rock phosphate) and carbon sources (dextrose, lactose, and sucrose). When tricalcium phosphate was substituted by rock phosphate, less soluble phosphate was produced. Glucose was the best carbon source used for solubilization of both tricalcium phosphate and rock phosphate, then followed by lactose and sucrose. Acidification of medium was not the major mechanism of phosphate solubilization by T. harzianum. Based on the ability of high phosphate solubilization, T. harzianum InaCC F88 is the most potential strain as a plant growth promoting fungus among the 10  isolates of T. harzianum Ina CC.  Key words:  biocontrol, Pikovskaya medium,  phosphate solubilization, Trichoderma harzianum